Pendampingan dalam Simulasi dan Peningkatan Pengetahuan Siswa Siswi Tentang Patah Tulang - Noor, Mohammad Arifin; Ansar, Ansar; Vandika, Arnes Yuli; Pannyiwi, Rahmat; Dunggio, Abdul Rivai Saleh; Saputra, M. Khalid Fredy (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Fracture is defined as a broken bone caused by trauma or physical force, and can occur due to excessive pressure compared to the bone's ability to withstand pressure. Injuries due to accidents in the school environment generally occur in the musculoskeletal system and must be treated quickly and appropriately. If not, it will cause more severe injuries and can trigger bleeding. To prevent injury to the musculoskeletal system, splint bandages are needed through Education. The purpose of this Community Service is to Assist and Improve Students' Knowledge About Bone Fractures with Simulation and as a learning that can determine the level of success of students in carrying out cardiopulmonary respiratory training in improving knowledge and skills. The health education method on fracture handling simulations so that students are able to make efforts to prevent disability and complications due to fractures and enable students to carry out initial examinations and initial treatment for fracture victims. The results of this activity received a good response from students as the target of community service activities. The conclusion that the implementation of community service followed by students showed an increase from sufficient knowledge to good knowledge. However, there needs to be monitoring and providing other materials so that it can motivate students to be more active and know about emergency handling.